Analisis Perputaran Persediaan Terhadap Kas Pada Perusahaan PT. Rocky Mitra Bangunan - Nurnaningsih Utiarahman (Gorontalo Management Research, 2018)
This research has a purpose to know the effect of inventory turnover to cash. Secondary data used in this research in the form of company financial statements of PT. Rocky Mitra Building period 2011-2013. Analytical methods used are qualitative and quantitative. The result of analysis from this research is inventory turnover can influence cash. The amount of inventory makes the cash reduced but if the inventory turnover also increases the amount of sales rose (cash sales) then the cash return will be faster